Derogar el Numeral 8 del Art. 110 del Código Civil Ecuatoriano en cuanto a las causales de Divorcio, ya que el Referido Numeral es Inconstitucional y Discriminatorio - Garrido Paladines, Oscar Adrián (2016)
In Article 110 paragraph 8 of the Civil Code as grounds for divorce established by the fact suffer one spouse of serious illness seen by three doctors appointed by the court as incurable and contagious or transmissible to offspring, this being contrary causal to the top to apply duties indicated therein. Art. 11, paragraph 2, clause 2 of our Constitution tells us that no one shall be discriminated against on grounds of ethnicity, place of birth, gender identity, marital status, socio-economic status, sexual orientation, health status, carry HIV, disability, physical difference or any other distinction, personal or collective to impair or abolish the recognition of the rights recognized in our Constitution all forms of discrimination is sanctioned. The grounds for divorce by serious illness is unconstitutional for the rights guaranteed in the Constitution of the Republic of Ecuador to in Article 11, paragraph 4 and 8 paragraph 2 in its order respectively tells us that no legal rule may restrict the rights and guarantees constitutional set out in the charter. Be unconstitutional any act or omission that diminishes regressive impair or abolish the preset exercise rights. Similarly, the current Constitution of our country prescribes rights the grounds for divorce by serious illness, in Art. 66 paragraph 4 of the Constitutional rule states that everyone has the right to formal equality, material and non- - 6 - discrimination of persons without exception and this causal serious illness impairs and infringes rights. For these reasons is unconstitutional divorce serious illness because equality of conditions has as a spouse, having thus inequality for his situation dignity against third and his family in particular, and also the rules must be clear is discriminated, precise and consistent to the Constitutional norm. This ensures the constitutional right mentioned in Art. 67 of the Constitution of the Republic of Ecuador that the State shall protect the family as the fundamental unit of society and ensuring the conditions that promote the full attainment of its purposes and provisions international conventions and treaties where Ecuador is part of them. If the Civil Code permits divorce for serious illness, considered incurable and contagious, goes against human dignity and restriction of rights guaranteed in the Constitution and in international human rights instruments to which should the law suit these treaties progressively for protection. Besides this ground it is obsolete because the practice has not been applied by the null cases the judicial function are not recorded, and its foundation of divorce are given for other reasons determined by the Civil Code. If divorce is permitted for serious illness goes against the purpose of marriage pointing Art. 81 of the Civil Code, as living together and mutual aid, this - 7 - inobserva solidarity that should exist between spouses, and compliance the obligations of faith saved, succor and help each other in all circumstances of life that guarantees civil law indicated. Similarly in the Ecuadorian Civil Code in its Arts.136, 138 respectively spouses are required to be saved faith, succor and help each other in all circumstances of life. The marriage is on equal rights and duties of the spouses, the spouses must be provided everything you need and will always be required to provide the other the help you need.